2012
DOI: 10.1371/journal.ppat.1002934
|View full text |Cite
|
Sign up to set email alerts
|

DENV Inhibits Type I IFN Production in Infected Cells by Cleaving Human STING

Abstract: Dengue virus (DENV) is a pathogen with a high impact on human health. It replicates in a wide range of cells involved in the immune response. To efficiently infect humans, DENV must evade or inhibit fundamental elements of the innate immune system, namely the type I interferon response. DENV circumvents the host immune response by expressing proteins that antagonize the cellular innate immunity. We have recently documented the inhibition of type I IFN production by the proteolytic activity of DENV NS2B3 protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
445
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(483 citation statements)
references
References 55 publications
19
445
1
Order By: Relevance
“…MITA is also a target molecule for microbial pathogens to escape the innate immune response. It has been shown that yellow fever virus, dengue virus, and hepatitis C virus nonstructure proteins target MITA to suppress MITA-mediated IFN induction (29)(30)(31)(32).…”
mentioning
confidence: 99%
“…MITA is also a target molecule for microbial pathogens to escape the innate immune response. It has been shown that yellow fever virus, dengue virus, and hepatitis C virus nonstructure proteins target MITA to suppress MITA-mediated IFN induction (29)(30)(31)(32).…”
mentioning
confidence: 99%
“…Differences in the ability of flaviviruses to counteract the type I IFN response between human and mouse cells have previously been reported (27)(28)(29). Phosphorylation of STAT1 and STAT2 proteins was previously shown to be blocked in human cells infected with natural strains of WNV (30)(31)(32), but STAT1 and STAT2 phosphorylation were not inhibited in the mouse cells ( Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Data from several studies have shown that counteraction of the host type I IFN response by flavivirus proteins differs between human and mouse cells. For example, dengue virus is able to counteract human but not mouse STAT2 and STING (27)(28)(29). Previous studies reported that an A30P substitution in the Kunjin WNV NS2A protein abrogated its ability to inhibit IFN signaling and attenuated rather than enhanced its virulence in mice (41).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulator of interferon genes (STING, also known as MITA, MPYS, and ERIS) is an ER-resident antiviral protein that has traditionally been thought to be a hub signaling adaptor for sensing cytosolic DNA viruses (8)(9)(10)(11)(12). More recently, it was reported that the NS2B3 protease of DENV could specifically cleave human STING in experimental models of DENV infection, thus linking STING to RNA viruses (13,14). However, DENV per se could not trigger the activation of the STING signaling.…”
mentioning
confidence: 99%